A sex‐balanced rodent model for evaluating phosphine inhalation toxicity. Issue 1 (3rd April 2020) - Tuet, Wing Y.; Racine, Michelle C.; Jennings, Laura; Pierce, Samuel A.; Tressler, Justin; McCranor, Bryan J.; Wong, Benjamin
Abstract: Exposure to phosphine (PH3 ), a common grain fumigant, is characterized by diverse nonspecific symptoms and a high mortality rate. Although PH3 poisoning is thought to target oxidative respiration, the exact mechanism of action remains largely unknown, resulting in limited treatment options. In our study, the effects of PH3 on female rats were assessed to elucidate potential sex‐specific differences and obtain a more comprehensive understanding of PH3 toxicity. Lethality, physiology, and behavior were evaluated in female rats exposed to gaseous PH3 (13, 200–26, 400 ppm × min), and results were compared with corresponding findings in male rats. Median lethal concentration‐time (LCt50 ) and time of death ( t TOD ) did not differ significantly between the sexes. Cardiopulmonary changes induced by PH3 were also of comparable magnitude, although temporally, respiratory responses occurred earlier and cardiovascular variations manifested later in female rats. Behavioral observations corroborated physiological findings and indicated a response to hypoxic conditions and low cardiac output. Together, these results provided insights on the toxic mechanisms of PH3, in particular, its potential interference with oxygen transport and circulation. Abstract : In our study, the effects of PH3 on female rats compared with earlier findings in male rats were assessed to elucidate potential sex‐specific differences and obtain a more comprehensive understanding of PH3 toxicity. Median lethal concentration‐time and time of death did not differ significantly between the sexes. Cardiopulmonary changes induced by PH3 were also of comparable magnitude, although temporally, respiratory responses occurred earlier and cardiovascular variations manifested later in female rats. Behavioral observations corroborated physiological findings and indicated a response to hypoxic conditions and low cardiac output.